MODEL BRANDING SPIRITUAL DALAM POSITIONING LEMBAGA PENDIDIKAN ISLAM DI ERA DIGITAL - Siti Fatimah; Hefniy; Khoiriyah (As-Sulthan Journal of Education, 2025)
This study examines the role of spiritual branding in determining the position of Islamic educational institutions in the digital era, focusing on SMAI Miftahul Arifin in Probolinggo. In the face of rapid technological developments, many Islamic educational institutions have difficulty utilizing digital platforms to convey their religious values. This study aims to investigate how SMAI Miftahul Arifin can utilize digital branding strategies to strengthen their image as an institution that prioritizes spiritual values. The method used is a mix-method, which combines qualitative approaches through case studies and quantitative with surveys to obtain a picture of public perception. The findings of the study indicate that although SMAI Miftahul Arifin has potential in spiritual branding, they have not succeeded in conveying these values ​​optimally through digital media. This study recommends that SMAI Miftahul Arifin develop a more structured and creative digital strategy, by creating more authentic and relevant content for their audiences, especially the younger generation. Overall, the results of this study confirm that the use of appropriate digital branding can strengthen SMAI Miftahul Arifin's position as an Islamic educational institution based on religious values ​​amidst digital competition.